Foreignization and Domestication Ideology of Indonesian Cultural Terms in Janda Dari Jirah Translated into English - Putu Cindy Aprilia Dewi; I Nengah Sudipa; Ida Ayu Made Puspani (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This study aims to identify and analyze the categories, translation methods, and translation ideology of Indonesian cultural terms in the novel Janda Dari Jirah translated into The Widow of Jirah. The method of collecting the data in this study was observation, meanwhile descriptive qualitative method was applied in analyzing the data. The theories of cultural categories, translation methods, and translation ideology were used to analyze the data. There are five categories of cultural terms found in the novel. Moreover, the translation methods applied by the translators were word-for-word translation, literal translation, faithful translation, semantic translation, adaptation, free translation, and idiomatic translation. With regards to the translation ideology, foreignization was more dominantly applied than domestication.